Reducing the Burden of Diarrhoea among Urban Households in Uganda - Barungi, Mildred; Kasirye, Ibrahim (Economic Policy Research Centre, 2012)
Diarrhoea remains a big challenge to attainment of water related Millennium Development Goals (MDGs) in Uganda. This brief examines the cost effectiveness of two water technologies in preventing Diarrhoea illness among urban households in Uganda. We estimate the reduction in the burden of disease arising from accessing either public stand-pipes or boreholes in urban areas. Details